The Framework of Analyzing Factors Influencing Green Purchase Intention for Indonesian Wet Wipes Consumers - Etik Endriyati, Farida; Permana, Dudi (Dinasti International Journal of Digital Business Management, 2023)
This framework study aims to analyze the role of Green Consumer Awareness, Willingness to Pay for Environment, Environmental Knowledge on Green Purchase Intention mediated by Green Commitment among Indonesian wet wipes users. This study examines individuals behave toward green items using the theoretical frameworks of theory triple bottom line and value belief norm theory. Green Consumer Awareness, Willingness to Pay for Environment, and Environmental Knowledge are expected to have a positive and significant effect on Green Commitment. In the relationship with Green Purchase Intention, it is expected result that Green Consumer Awareness, Willingness to Pay for Environment, Environmental Knowledge and Green Commitment have a positive and significant effect on Green Purchase Intention. Green Commitment is expected to have a positive and significant mediating influence between Green Consumer Awareness, Willingness to Pay for the Environment, Environmental Knowledge to Green Purchase Intention.